2010
DOI: 10.1016/s1885-5857(10)70005-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Body Weight: Longitudinal Analysis of the SUN Cohort

Abstract: Introduction and objectives. Our aim was to investigate prospectively the association between two major cardiovascular risk factors: smoking and weight gain.Methods. We prospectively evaluated 7565 individuals taking part in a dynamic cohort study over a median follow-up period of 50 months. Self-reported weight and physical activity levels had been validated previously. The adjusted mean difference in weight gain relative to neversmokers (the reference group) was estimated for different levels of tobacco expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…showing that recent ex-smokers and active smokers both experienced significantly greater weight gains than never-smokers (Basterra-Gortari et al, 2010). In this sense, exposure to cigarette smoke condensate induces changes in histone modifications in epithelial cells and immortalized bronchial epithelial cells (Liu et al, 2010), suggesting that epigenetics could play a role in smoking-cessation-induced weight gain.…”
Section: Endocrine Disruptors and Toxicsmentioning
confidence: 95%
“…showing that recent ex-smokers and active smokers both experienced significantly greater weight gains than never-smokers (Basterra-Gortari et al, 2010). In this sense, exposure to cigarette smoke condensate induces changes in histone modifications in epithelial cells and immortalized bronchial epithelial cells (Liu et al, 2010), suggesting that epigenetics could play a role in smoking-cessation-induced weight gain.…”
Section: Endocrine Disruptors and Toxicsmentioning
confidence: 95%
“…Since the fear of gaining weight might be an important barrier to quit smoking, a better understanding of this complex relationship is needed. Recent longitudinal studies indicated that the excess weight gain following smoking cessation is probably transient and tends to occur shortly after cessation (Reas et al, 2009;Basterra-Gortari et al, 2010) but large scale studies are required to confirm these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of studies have examined weight change among quitters in relation to never-smokers, with conflicting results. Some indicate that quitters do not gain significantly more weight than never-smokers in the long term (Reas et al, 2009;Travier et al, 2012), while others suggest that quitters gain significantly more weight than never-smokers (Basterra-Gortari et al, 2010;Flegal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The existing longitudinal research has a number of important weaknesses, including the inability to control adequately for baseline BMI (Owen-Smith & Hannaford, 1999;Reas et al, Advance Access publication January 24, 2014 nicotine & tobacco research, Volume 16, number 6 (June 2014) 867-871 2009), and reliance on self-reported or retrospective reports of weight (Basterra-Gortari et al, 2010;Flegal et al, 1995;Owen-Smith & Hannaford, 1999;Reas et al, 2009;Travier et al, 2012) or smoking status (Flegal et al, 1995;Williamson et al, 1991). Some findings may have limited generalizability to the general population of smokers since cohorts were drawn from health service users (Owen-Smith & Hannaford, 1999;Travier et al, 2012) or university graduates (Basterra-Gortari et al, 2010), hence the need for further research (Fernández & Chapman, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation